Dampak Pengalaman Pasien yang Mempengaruhi Loyalitas Pasien di Rumah Sakit - Masjadi, Masjadi; Jannah, Safira Salsabilul (Wiraraja Medika : Jurnal Kesehatan, 2025)
Patient loyalty is an important indicator of hospital success. This loyalty not only leads to repeat visits, but can also improve the hospital's reputation in the eyes of the community. A study shows that patients who feel satisfied with healthcare services are likely to recommend the hospital to others, which contributes to an increase in the number of new patients. This suggests that a good patient experience can be an effective marketing tool. So this study was conducted to determine the patient experience factors that influence loyalty and how hospitals can improve patient experience. Methods: This study included a systematic literature review. Which this article uses a prism diagram to sort articles. By using platforms such as google schoolar, suitable articles were found. Results: The results of analyzing 17 articles that have been found, it is known that all articles show the influence between patient experience and patient loyalty in hospitals. All of them conveyed that there was a significant relationship between the two.